Drugs Targeting Epigenetic Modifications and Plausible Therapeutic Strategies Against Colorectal Cancer - Patnaik, Srinivas; Anupriya, (Frontiers in Pharmacology, 2019)
Genetic variations along with epigenetic modifications of DNA are involved in Colorectal Cancer (CRC) development and progression. CRC is the fourth leading cause of cancer related deaths worldwide. Initiation and progression of CRC is the cumulation of a variety of genetic and epigenetic changes in colonic epithelial cells. Colorectal carcinogenesis is associated with epigenetic aberrations including DNA methylation, histone modifications, chromatin remodeling and non-coding RNAs. Recently, epigenetic modifications have been identified like association of hypermethylated gene Claudin11 (CLDN11) with metastasis and prognosis of poor survival of CRC. DNA methylation of genes CMTM3, SSTR2, MDFI, NDRG4 and TGFB2 is potential epigenetic biomarkers for the early detection of CRC. Tumor suppressor candidate 3 (TUSC3) mRNA expression is silenced by promoter methylation which promotes EGFR signaling and rescues the CRC cells from apoptosis and hence leading to poor survival rate. Previous scientific evidences strongly suggest epigenetic modifications which contribute to anticancer drug resistance. Recent research studies emphasize development of drugs targeting Histone Deacetyalses (HDAC), DNA Methyltransferase inhibitors is an emerging anticancer strategy. This review covers potential epigenetic modification targeting chemotherapeutic drugs and probable implementation for the treatment of CRC which offer a strong rationale to explore therapeutic strategies and provides a basis to develop potent antitumor drugs.